Near-optimal supervisory control of flexible manufacturing systems using divide-and-conquer iterative method. (23rd March 2016) - Zhao, Mi; Uzam, Murat; Hou, YiFan
This article proposes an iterative deadlock resolution method for flexible manufacturing systems modeled with G -systems. To design a non-blocking controlled system with maximally permissive behavior in a G -system ( GS ), a reachability graph-based analysis technology is utilized. Since the reachability graph of a large-scale GS easily becomes unmanageable, an optimal non-blocking supervisor becomes a challenging problem in a GS . To facilitate this problem, the Divide-and-Conquer approach is a good choice for complex G -systems. First, an uncontrolled GS resolves into a number of associated subnets. Then, every subnet suffering from deadlocks is utilized to design the liveness-enforcing supervisor for the original GS . Thus, additional monitors can be obtained if the liveness of all subnets is achieved. Subsequently, a partially controlled GS is derived by including all monitors within the GS, and its liveness can be ensured by designing a new set of monitors. Consequently, a non-blocking GS is derived. The major advantage of the proposed method is that a non-blocking supervisor with near-optimal behavioral permissiveness can be obtained in general. Finally, a typical GS example popularly studied in the literature is applied to demonstrate the validity and the availability of the method in this article.